LONG-DISTANCE COMMUTING: LABOR DECISIONS IN NORTH SUMATERA - Sylvia Vianty Ranita; Andri Herlambang (SEAN Institute, 2023)
Cross-border labor mobility is currently a sight we are used to seeing on a daily basis. The increase in labor mobility is seen with the increase in commuter workers, especially for longer trips that occurred in North Sumatra from 2015 to 2018. This increase in travel activity also has an influence on economic growth between regions. But unfortunately, until now, there are almost no studies or analyses related to labor mobility, especially commuter activities for long-distances in North Sumatra. The purpose of this study was to identify how much labor in North Sumatra tends to travel long-distances and compare the impact of public transportation and income on the decision to do long-distance commuting in North Sumatra. This research uses an economic approach, especially on the use of occupational models in analyzing labor decisions to commute. Sakernas 2018 data were used in this study using logistic regression analysis techniques and logit models. The findings in this study show that the decision to commute for a distance of more than 30 km one way by utilizing public transportation has a tendency to be 2.9 times greater than the variable income in North Sumatra compared to workers who travel to work on other distances. This research shows that public transportation is an important bridge for workers to carry out mobility between regions and as an effort to increase economic growth,